Effect of nickel on growth and biochemical characteristics of wheat (Triticum aestivum L.) seedlings. (1st March 2016) - Uruç Parlak, Kadiriye
Abstract: A hydroponic experiment was carried out under controlled conditions to investigate the impact of different levels of nickel (Ni) in the nutrient solution on growth and biochemical characteristics of wheat ( Triticum aestivum L.) seedlings, including membrane lipid peroxidation (LPO), proline accumulation and superoxide dismutase (SOD). The Ni levels investigated were 0, 25 and 50 μg per litre. A statistically significant increase in LPO was recorded in the seedlings grown at concentrations of 25 or 50 μg Ni per litre, but SOD (1.15.1.11) activity was not significantly affected. Plant height and chlorophyll content were affected significantly in a dose dependent manner. Proline content increased considerably in response to Ni concentration. The results indicate that the increase in the activities of the antioxidant enzymes were not sufficient to protect cell membrane against Ni toxicity.